[tex]1)a - b[/tex]
[tex]15 - 76 = - 61 \\ 34 - ( - 47) = 34 + 47 =81 \\ - 13 - ( + 38) = - 13 - 38 = - 51 \\ - 6 - ( - 9) = - 6 + 9 = 3[/tex]
[tex]2)b - a[/tex]
[tex]76 - 15 = 61 \\ - 47 - 34 = - 81 \\ 38 - ( - 13) = 38 + 13 = 51 \\ - 9 - ( - 6) = - 9 + 6 = - 3[/tex]
[tex]3) |a| - |b| [/tex]
[tex] |15| - |76| = 15 - 76 = - 61 \\ |34| - | - 47| = 34 - 47 = - 13 \\ | - 13| - | + 38| = 13 - 38 = - 25 \\ | - 6| - | - 9| = 6 - 9 = - 3[/tex]
[tex]4)( - a) - ( - b) [/tex]
[tex]-15-(-76)=-15+76=61[/tex]
[tex]-34-[-(-47)]=-34-47=-81[/tex]
[tex]-(-13)-(-38)=13+38=51[/tex]
[tex]-(-6)-[-(-9)]=6-9=-3[/tex]